THE EFFECT OF INNOVATION ON EMPLOYEE PERFORMANCE AT THE PAMONG PRAJA POLICE UNIT OFFICE (SATPOL PP) BULUNGAN REGENCY - Wempi Feber; Iskandar Iskandar (LPSDI Bina Patria, 2023)
This study aims to determine whether motivation affects the performance of employees at the Civil Service Police Unit (Satpol PP) Bulungan Regency. The population in this study were all employees of the Civil Service Police Unit (Satpol PP) Bulungan Regency, amounting to 74 people, and the sample in this study was 74 people using saturated sampling technique or census. This type of research is quantitative with a survey approach. To collect data the researchers used interview techniques, questionnaires, observation, literature studies and documentation studies. Furthermore, the data that has been collected is processed by data processing techniques such as: editing, coding, scoring, and tabulating, and analyzed by means of simple regression analysis. Based on the results of the validity and reliability test of the independent variable data (X) with the dependent variable (Y), the questionnaire data used was proven to be valid and reliable so that no case data was excluded (excluded). The form of the regression line equation of the 2 (two) research variables used is Y = 14.318 + 0.261X. Based on the significance used in this study, which is 0.05, which is then compared with the significance value at the output, it can be concluded that partially motivation has a significant effect on employee performance with a comparison of the significance value of 0.006 <0.05.